Timing, reward processing and choice behavior in four strains of rats with different levels of impulsivity. - Garcia Aguirre, Ana I. (Kansas State University, 2011)
Several studies have examined timing and impulsive choice behavior in spontaneously hypertensive rats (SHR) as a possible pre-clinical model for Attention Deficit Hyperactivity Disorder (ADHD). However, the strain has not been specifically selected for the traits of ADHD and as a result their appropriateness as a model has been questioned. This study investigated whether SHR would exhibit timing deficits, poor reward processing and impulsive behavior in comparison to the Wistar Kyoto (WKY) control strain in a discrete-trial choice task. In addition, as a first approach to find another potential animal model of ADHD, we evaluated a strain that has shown high levels of impulsivity, the Lewis (LEW) rats and compared them with the Wistar (WIS) rats. In the first phase of the experiment, rats could chose a lever associated with a Smaller-sooner (SS) reward of 1 pellet delivered after 10 s and a Larger-later (LL) reward of 2 pellets delivered after 30 s. Subsequently, the rats were exposed to different phases, where the reward on the LL choice was increased to 3 and 4 pellets and where the delay to the SS choice was increased to 15 and 20 s. The SHR and WKY strains did not differ in their timing or choice behavior. In comparison to WIS, LEW showed timing deficits in both manipulations and deficits in choice behavior in the delay manipulation, indicating deficits in time processing. Individual differences among the rat within a strain accounted a significant proportion of the total variance and contributed more variance than the strain of the rat. These results indicate that the SHR and LEW strains are not sufficiently homogeneous with respect to impulsive choice behavior to be considered as viable models for impulse control disorders such as ADHD.
Keywords: Timing; Reward Processing; Choice Behavior; Impulsivity; Wistar Kyoto (WKY) rats; Spontaneously Hypertensive Rats (SHR); Psychology, Behavioral (0384)